Leadership practices of physical education teachers and student-related outcomes: a systematic mixed method review and analysis - Kim, Hyun-Duck; Cruz, Angelita Bautista (Frontiers in Psychology, 2024)
Introduction This study systematically reviewed and analyzed both qualitative and quantitative studies that focused on the relationship between physical education (PE) teachers’ leadership and student outcomes using data mining and meta-analysis. Methods Using the Scopus, PsycINFO, PubMed, and SPORTDiscus databases, text data from the included 150 relevant articles were examined through a text data mining approach. Quantitative and mixed-method studies were then further evaluated, yielding 49 articles eligible for inclusion in the meta-analysis. Results Findings from the data-mining analysis using Leximancer revealed eight major themes associated with PE teacher leadership, emphasizing motivation, education, support, and teaching. Results from the meta-analysis using the Comprehensive Meta-Analysis software showed that autonomy-supporting behaviors showed strong positive effects on student satisfaction, motivation, competence, and engagement. Regional differences in research focus were observed, with health being less emphasized in Asian and European studies. Student sex emerged as a moderating factor. Conclusion The study highlights the role of PE teacher leadership and the convergence/divergence among research findings. Moreover, applying the HDST approach to synthesize both qualitative and quantitative articles provided a deeper and more comprehensive understanding of leadership within the PE field.